COSMOPOLITANISM AND DEMOCRACY BEYOND STATES: THE COSMOPOLITAN DEMOCRACY PROJECT - Medina, Ricardo Norberto (European Scientific Journal, ESJ, 2014)
Today we are facing a period of profound social and political transformation on a global scale, under the inevitable process of globalization. This brings an important debate about how to properly organize the international society in order to contribute to the resolution of global problems. Among these global problems we can highlight the crisis of the nation state in a world where states by themselves can no longer provide security for citizens who call for greater representation and democratic participation, meanwhile telecommunications technology allows a human interconnectedness that has no precedents in history. The fact is that international society is changing into a new world order that is not clearly defined yet. To face this reality, the cosmopolitan democracy project proposes updating the Kantian cosmopolitanism through a broad legal and political program that includes not only the democratic reform of governance institutions but the peaceful transformation of the world order as well. However, political realism considers illusory this project, as any other that tries to organize the international society according to regulative ideals. In response to this criticism, I consider extremely important the promotion of an appropriate education that enables to subvert the realism and help us to recognize our sense of belonging to a plural and diverse world, allowing this way the empowerment of the world citizenship and making possible a genuine cosmopolitan democracy in the twenty-first century.